Analisis Pengaruh Pejalan Kaki Yang Menyeberang Jalan Pada Fasilitas Penyeberangan Zebra Cross Terhadap Panjang Antrian Kendaraan - Sweetly Manopo; Semuel Yacob Recky Rompis; Joice Elfrida Waani (Universitas Negeri Gorontalo, 2022)
The increase number of vehicles is not the main factor causing congestion. There are other factors, such as the movement of pedestrians crossing the road using a zebra cross. This study aims to determine the effect of pedestrians crossing on vehicle queue lengths using shock wave analysis, and evaluate whether zebra cross facilities are still suitable for use or not at research site. This research was conducted for 4 days on Sam Ratulangi street in front of Multimart Ranotana Manado City. Data analysis uses traffic characteristics correlation of volume, speed and density. The characteristic correlation that will be used for the shock wave analysis calculation is based on the highest coefficient of determination (R2). The results of the study, based on shock wave analysis showed that pedestrians crossing could make a vehicle queue length of 33.5 meters for the left lane and 74.6 meters for the right lane. Based on the average number of pedestrians crossing the volume of vehicles and the number of conflicts that occur (PV2), it is recommended that the type of crossing facility is pelican with a protector. The greater duration of pedestrians crossing (r) then the maximum queue length of vehicles (Qm) will be greater.